2014
DOI: 10.1371/journal.pone.0095900
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Retinotoxicity Is Prevented by Gene Transfer of a Soluble Interleukin-17 Receptor Acting as a Cytokine Blocker: Implications for Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a common yet complex retinal degeneration that causes irreversible central blindness in the elderly. Pathology is widely believed to follow loss of retinal pigment epithelium (RPE) and photoreceptor degeneration. Here we report aberrant expression of interleukin-17A (IL17A) and the receptor IL17RC in the macula of AMD patients. In vitro, IL17A induces RPE cell death characterized by the accumulation of cytoplasmic lipids and autophagosomes with subsequent activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 43 publications
5
49
0
Order By: Relevance
“…In conclusion, our results indicate that IL-17 + cells are invariably present in GA lesions but not observed in age-matched control sections confirming earlier studies of increased IL-17 staining in GA [31,32]. Our study identifies T lymphocytes as an important source of IL-17 in GA. We also showed that IBA-1 + monocytes/macrophages participate in the IL-17 production in the choroid of GA patients.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, our results indicate that IL-17 + cells are invariably present in GA lesions but not observed in age-matched control sections confirming earlier studies of increased IL-17 staining in GA [31,32]. Our study identifies T lymphocytes as an important source of IL-17 in GA. We also showed that IBA-1 + monocytes/macrophages participate in the IL-17 production in the choroid of GA patients.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, our observations suggest that T cells and monocytes/macrophages could be responsible for the significant elevation of IL-17 mRNA in maculae of eyes of AMD patients compared to control eyes [34]. It is yet unclear if and how IL-17 contributes to the pathological processes of GA. IL-17 has been shown to directly deteriorate RPE in vitro [32,35]. Moreover, IL-17 production has been associated with retinal and RPE lesions in a Nrf2-/- mice model of AMD [36] in vivo, and IL-17 could contribute to RPE degeneration in GA.…”
Section: Resultsmentioning
confidence: 99%
“…The elevation of IL-17A expression was found not only in the peripheral blood but also in macular tissues with AMD lesions. [17][18][19] Since AMD patients usually present without systemic inflammation, we hypothesized that local IL-17A signaling was more relevant in AMD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…32 The elevated expression of IL-17RC recently was observed in chorioretinal tissues from AMD patients. 17 Therefore, the RPE cells, being resident at the chorioretinal interface, would appear a potential target of IL-17A immunologic effect. A recent report showed that IL-17A promoted ARPE-19 cells to secrete inflammatory mediators and compromised the ARPE-19 monolayer barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation